Big Nate : in a class by himself - Peirce, Lincoln (New York, N.Y. : Harper, 2010)
Supremely confident middle school student Nate Wright manages to make getting detention from every one of his teachers in the same day seem like an achievement.
Maine author.
Keywords: Middle schools -- Juvenile fiction; Conduct of life -- Juvenile fiction; Schools -- Juvenile fiction; Humorous fiction